Reducing effects of isoliquiritigenin, a naturally occurring GABAB receptor agonist, on alcohol-motivated behaviors in alcohol-preferring rats - Paola Maccioni; Laura Regonini Somenzi; Mauro A. M. Carai; Federico Corelli; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2026)
Rationale and objectives Glycyrrhiza glabra L. (Fabaceae; licorice) is a widely used medicinal herb known to exert protective effects against multiple neurological diseases. The flavonoid, isoliquiritigenin (ISL), is a main constituent of roots of Glycyrrhiza glabra . ISL has been reported to behave as a GABA B receptor agonist and exert multiple pharmacological effects. Given the role of the GABA B receptor in the neurobiological and pharmacological bases of alcohol use disorder, the present study investigated the effect of ISL on a series of alcohol-related behaviors in selectively bred, female Sardinian alcohol-preferring rats. Methods and results The collected results indicated that acute treatment with ISL (5-20 mg/kg, i.p.; 50-200 mg/kg, i.g.) decreased operant oral alcohol self-administration under both fixed and progressive ratio schedules of reinforcement and suppressed cue-induced reinstatement of alcohol seeking. ISL effect on alcohol self-administration was partially blocked by pretreatment with the GABA B receptor antagonist, SCH50911, and potentiated by co-administration of the positive allosteric modulator of the GABA B receptor, GS39783. Acute treatment with doses of ISL as high as 80 mg/kg (i.p.) did not alter spontaneous locomotor activity, suggestive of the specificity of ISL effects on alcohol-related behaviors. Conclusions These results confirm the ability of ISL to behave in vivo as a GABA B receptor agonist; they also indicate that ISL reproduced the suppressing effects of the prototypic GABA B receptor agonist, baclofen, on multiple alcohol-related behaviors in rodents.

Reducing effect of intragastrically administered saikosaponin A on alcohol and sucrose self-administration in rats - Paola Maccioni; Young-Won Chin; Federico Corelli; Hak Cheol Kwon; Giancarlo Colombo (Natural Product Research, 2023)

Reducing effect of the novel positive allosteric modulator of the GABAB receptor, COR659, on binge-like alcohol drinking in male mice and rats - Irene Lorrai; Chase Shankula; Jorge Marquez Gaytan; Tomoya Kawamura; Paola Maccioni; Claudia Mugnaini; Federico Corelli; Gian Luigi Gessa; Pietro Paolo Sanna; Giancarlo Colombo (Psychopharmacology, 2022)

Suppressing effect of COR659 on alcohol, sucrose, and chocolate self-administration in rats: involvement of the GABAB and cannabinoid CB1 receptors - Paola Maccioni; Giancarlo Colombo; Irene Lorrai; Alessandro Zaru; Mauro A. M. Carai; Gian Luigi Gessa; Antonella Brizzi; Claudia Mugnaini; Federico Corelli (Psychopharmacology, 2017)

Inhibition of alcohol self-administration by positive allosteric modulators of the GABAB receptor in rats: lack of tolerance and potentiation of baclofen - Paola Maccioni; Daniela Vargiolu; Andrew W. Thomas; Pari Malherbe; Claudia Mugnaini; Federico Corelli; Kimberly A. Leite-Morris; Gian Luigi Gessa; Giancarlo Colombo (Psychopharmacology, 2015)